2023
DOI: 10.35848/1347-4065/ace145
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PTFE particle size in designing BaTiO3 dielectric composites under the cold sintering process

Abstract: The Cold Sintering Process (CSP) can provide opportunities to fabricate high-performance BaTiO3 dielectric composites with polymer materials that are typically difficult to impossible to co-process under a conventional sintering process. Therefore, we investigated the preparation process of BaTiO3 sintered body by CSP and integrated a well-dispersed intergranular polymer phase. In this study, we focused on preparing BaTiO3 and Polytetrafluoroethylene (PTFE) composites. We considered the importance of the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…It was found that these materials could be sintered at low temperatures to an overall high density of ∼94% to 98% Recently, Nunokawa et al showed that with better mixing and dispersion of finer PTFE particles, BaTiO 3 PTFE composites with similar properties to the PPO composites could be realized. 32) The uniformity of the polymer is extremely important for obtaining a higher breakdown strength and time-dependent degradation resistance properties: like all mechanical or electric breakdown phenomena the fields can always find the weak points and therefore control the breakdown strength.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that these materials could be sintered at low temperatures to an overall high density of ∼94% to 98% Recently, Nunokawa et al showed that with better mixing and dispersion of finer PTFE particles, BaTiO 3 PTFE composites with similar properties to the PPO composites could be realized. 32) The uniformity of the polymer is extremely important for obtaining a higher breakdown strength and time-dependent degradation resistance properties: like all mechanical or electric breakdown phenomena the fields can always find the weak points and therefore control the breakdown strength.…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35] Additionally, an undeniable advantage that cold sintering has over other novel sintering techniques 36 is that cold sintering can be used to process hard and soft materials together in one step in order to produce novel interfaces that improve properties like breakdown strength and device reliability. 9,37 Advances in cold sintering science will be accelerated by the ability to measure and monitor, in real-time, the evolution of complex interfaces and dissolution/precipitation interactions. 38 Currently, progress in these areas is complicated by processing materials in opaque dies.…”
Section: Introductionmentioning
confidence: 99%